Internal legal protection of the trademark - BOUBETRA, Tarek (Journal of Human Sciences, 2020)
A trademark is one of the most important elements of intellectual property in general and industrial property in particular, a signal that traders place to distinguish their goods or services from those of other goods and services, thereby making the consumer prefer a good or service from the other, thus achieving significant financial gains, and Through this feature, the trademark has become the target of imitators for material gain, which led to the State to recognize the domestic legal protection through the order 03-06 on trademarks as a result of attacks on them from imitation and misleading to harm the consumer and the right holder and State all either.